Remarks on the Ancient Bactrian Title Kavi (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In the second half of the 19th century and the beginning of the 20th century, large-scale scientific research was carried out by European historians on the history of the first statehood and the emergence of management titles in Central Asia. M. Dunker , V. Geiger , E. Reich , V. Tomashek , J. Prashek , I.V. Pyankov , V.A. Liveshits , V.G. Lukonin , E. Bikerman , V. Tarn , O. Boperrachi , R. Gardner  such scholars dealt with issues of the history of early statehood and management and provided information about the existence of political associations and the title of ruler in the territory of Central Asia until the Achaemenid period. They mainly relied on written sources and archeological materials left by Avesta and Greco-Roman historians.